C1q/tumour necrosis factor-related protein-3 alleviates high-glucose-induced lipid accumulation and necroinflammation in renal tubular cells by activating the adenosine monophosphate-activated protein kinase pathway. (August 2022) - Du, Chunyang; Zhu, Yan; Yang, Yan; Mu, Lin; Yan, Xue; Wu, Ming; Zhou, Chenming; Wu, Haijiang; Zhang, Wei; Wu, Yanhui; Zhang, Guoyu; Hu, Yue; et al.
Abstract: Lipid accumulation and progressive necroinflammation play pivotal roles in the development of diabetic nephropathy. C1q tumour necrosis factor-related protein-3 (CTRP3) is an adipokine with pleiotropic functions in cell proliferation, glucose and lipid metabolism, and inflammation. However, the mechanism and involvement of CTRP3 in lipid metabolism and the necroinflammation of renal tubular cells remain unclear. Here, we report that CTRP3 expression decreased in a time- and concentration-dependent manner in high glucose-stimulated HK-2 cells. We noted that the overexpression of CTRP3 or recombinant CTRP3 (rCTRP3) treatment prevented high glucose-induced lipid accumulation by inhibiting the expression of sterol regulatory element-binding protein-1 and increasing the expression of peroxisome proliferator-activated receptor-α and ATP-binding cassette A1. Moreover, the nucleotide-binding oligomerisation domain-like receptor protein 3-mediated inflammatory response and mixed lineage kinase domain-like protein-dependent necroinflammation were inhibited by CTRP3 overexpression or rCTRP3 treatment in HK-2 cells cultured in high glucose. Furthermore, lipotoxicity-induced by palmitic acid was found to be involved in necroinflammation in HK-2 cells, and CTRP3 displayed the same protective effect. CTRP3 also activated the adenosine monophosphate-activated protein kinase (AMPK) pathway, whereas adenine 9-β-D -arabinofuranoside, an AMPK inhibitor, replicated the protective effects of CTRP3. Besides, using kidney biopsies from patients with diabetes, we found that decreased CTRP3 expression was accompanied by increased lipid deposition, as well as the structural and functional injury of renal tubular cells. Our findings demonstrate that CTRP3 affects lipid metabolism and necroinflammation in renal tubular cells via the AMPK signalling pathway. Thus, CTRP3 may be a potential therapeutic target in diabetic renal injury.